Applied anatomy of the submental island flap and its clinical application in the repair of defects following hypopharyngeal carcinoma resection. Issue 1 (1st September 2015) - Chen, Xi; Zhou, Han; Zhang, Yong‐Jie; Yin, Lin; Lu, Mei‐Ping; Xing, Guang‐Qian; Lin, Zi‐Ping; Cheng, Lei
Abstract: Objective: To explore the feasibility of the submental island flap in the repair of hypopharyngeal defects. Methods: We collected wet specimens of fresh cadaveric heads from the Han Chinese adult population for applied anatomy of the submental island flap, and followed five patients with pyriform sinus carcinoma after reconstruction surgery using submental island flaps. Results: We found that the average length and width of the submental island flaps were (65.20 ± 11.69) mm and (46.70 ± 6.59) mm, respectively. The skin flap in all five patients survived after surgery, and tracheal tubes and gastric tubes were removed 7–36 days after surgery. Patients were followed up for 24–42 months, pharyngeal flaps grew well, and speech and swallowing functions were satisfactory. Conclusion: The submental island flap is a preferred material for the repair of hypopharyngeal defects after hypopharyngeal carcinoma resection, because of good blood supply, easy harvesting, and high survival rate.